Iridium-catalyzed asymmetric hydrogenation of racemic α-substituted lactones to chiral diols. Issue 3 (28th November 2016) - Yang, Xiao-Hui; Yue, Hai-Tao; Yu, Na; Li, Yi-Pan; Xie, Jian-Hua; Zhou, Qi-Lin
Abstract : A protocol for the highly efficient iridium-catalyzed asymmetric hydrogenation of racemic α-substituted lactones via dynamic kinetic resolution is described. Abstract : We report a protocol for the highly efficient iridium-catalyzed asymmetric hydrogenation of racemic α-substituted lactones via dynamic kinetic resolution. Using Ir-SpiroPAP ( R )-1d as a catalyst, a wide range of chiral diols were prepared in a high yield (80–95%) with a high enantioselectivity (up to 95% ee) under mild reaction conditions. This protocol was used for enantioselective syntheses of (−)-preclamol and a chiral 2, 5-disubstituted tetrahydropyran.